Analisis Ketimpangan Pembangunan Di Kawasan Banua Anam ditinjau Dari Aspek Ekonomi, Sosial, dan Anggaran - Aldi; Ahmad Yunani (PPJP ULM, 2020)
The purpose of this study is (1) to find out the Development Inequality inthe Banua Anam Region (2) See the Inequality in the Development of the BanuaAnam Region (2) Which regency has the highest and lowest IPD. The methodused in this research is quantitative descriptive analysis and Analysis ofDevelopment Planning Techniques. The results of the Tabalong and BalanganResearch included developed but depressed areas for Tapin. Hulu SungaiSelatan, Hulu Sunga Tengah, and Hulu Sungai Utara enter developed areas,including developing regions. Inequality in the Banua Anam region is still high;areas of increasing inequality are Tabalong and Balangan. Economic Aspectsare the most dominant in creating imbalance. The highest RegionalDevelopment Indexes are Tabalong, Balangan, and Tapin,